IVIM diffusion-weighted imaging of the liver at 3.0 T: Comparison with 1.5 T. (2015) - Cui, Yong; Dyvorne, Hadrien; Besa, Cecilia; Cooper, Nancy; Taouli, Bachir
Abstract: Purpose: To compare intravoxel incoherent motion (IVIM) diffusion-weighted imaging (DWI) of the liver between 1.5 T and 3.0 T in terms of parameter quantification and inter-platform reproducibility. Materials and methods: In this IRB approved prospective study, 19 subjects (17 patients with chronic liver disease and 2 healthy volunteers) underwent two repeat scans at 1.5 T and 3.0 T. Each scan included IVIM DWI using 16 b values from 0 to 800 s/mm 2 . A single observer measured IVIM parameters for each platform and estimated signal to noise ratio (eSNR) at b 0, 200, 400 and 800 s/mm 2 . Wilcoxon paired tests were used to compare liver eSNR and IVIM parameters. Inter-platform reproducibility was assessed by calculating within-subject coefficient of variation (CV) and Bland–Altman limits of agreement. An ice water phantom was used to test ADC variability between the two MRI systems. Results: The mean invitro difference in ADC between the two platforms was 6.8%. eSNR was significantly higher at 3.0T for all selected b values ( p = 0.006–0.020), except for b 0 ( p = 0.239). Liver IVIM parameters were significantly different between 1.5 T and 3.0 T ( p = 0.005–0.044), except for ADC ( p = 0.748). The inter-platform reproducibility of true diffusion coefficient ( D ) and ADC were good, with mean CV of 10.9% and 11.1%, respectively. Perfusion fraction (PF) and pseudodiffusion coefficient ( D *) showed more limited inter-platform reproducibility (mean CV of 22.6% for PF and 46.9% for D *). Conclusion: Liver D and ADC values showed good reproducibility between 1.5 T and 3.0 T platforms; while there was more variability in PF, and large variability in D * parameters between the two platforms. These findings may have implications for drug trials assessing the role of IVIM DWI in tumor response and liver fibrosis.